A Novel Trypsin and Chymotrypsin Inhibitor from Maclura pomifera Seeds - Lazza, Cristian Martin (2010)
A new peptidic protease inhibitor (MpI) has been isolated from Maclura pomifera seeds, being the first trypsin and chymotrypsin inhibitor from a species belonging to the family Moraceae. MpI was purified by acetone precipitation, gel filtration and ion exchange chromatography, successively, with purification factors of 112 and 109 for the aforementioned enzymes, which are infrequent high values for inhibitors isolated from seeds. MpI showed a unique band in SDSTricine PAGE (Mr 11 kDa) and isoelectric focusing (pI = 5.2), inhibited the serine proteases trypsin and -chymotrypsin(IC50 0.17 and 0.7 μg/ml, respectively), but not cathepsin B (cysteine protease), cathepsin D (aspartic protease) nor carboxypeptidase A (metallo protease). The N-terminal sequence was determined (AREPKFSTHCEEEESR) but no homology was detected with other peptide inhibitors isolated from seeds. Preliminary assays related to blood clotting reactionsshowed that the isolated inhibitor significatively increased the activated partial thromboplastin time (APTT), suggesting its potential use in the treatment of blood coagulation disorders.